Genetically modified (GM) late blight-resistant potato and consumer attitudes before and after a field visit - Jéssica Bubolz; Patrycja Sleboda; Anna Lehrman; Sven-Ove Hansson; Carl Johan Lagerkvist; Björn Andersson; Marit Lenman; Svante Resjö; Marc Ghislain; Muhammad Awais Zahid; Nam Phuong Kieu; Erik Andreasson (GM Crops & Food, 2022)
Late blight, caused by Phytophthora infestans, is the most devastating disease in potato production. Here, we show full late blight resistance in a location with a genetically diverse pathogen population with the use of GM potato stacked with three resistance (R) genes over three seasons. In addition, using this field trials, we demonstrate that in-the-field intervention among consumers led to change for more favorable attitude generally toward GM crops.